Refining Spirit Hermeneutics - Keener, Craig S. (Pneuma, 2017)
In this article Craig S. Keener participates in the roundtable dialogue on his book: Spirit Hermeneutics: Reading Scripture in the Light of Pentecost. After responding individually to the reviews of L. William Oliverio, Jr., Kevin L. Spawn, Hannah R.K. Mather, Ben Aker, Jacqueline N. Grey, and Kenneth J. Archer, Keener responds more fully to some key issues in the reviews and articulates elements of his hermeneutical theory that complement the arguments in his book, including discussions on conventional hermeneutics, the role of subjectivity/objectivity in interpretation, and the relationship between pentecostal hermeneutics and evangelical hermeneutics.